Antioxidant and Anti-Inflammatory Activity of Cynanchum acutum L. Isolated Flavonoids Using Experimentally Induced Type 2 Diabetes Mellitus: Biological and In Silico Investigation for NF-κB Pathway/miR-146a Expression Modulation - Reda F. A. Abdelhameed; Amany K. Ibrahim; Mahmoud A. Elfaky; Eman S. Habib; Mayada I. Mahamed; Eman T. Mehanna; Khaled M. Darwish; Dina M. Khodeer; Safwat A. Ahmed; Sameh S. Elhady (MDPI AG, 2021)
Cynanchum acutum L. is a climbing vine that belongs to the family Apocynaceae. Using different chromatographic techniques, seven compounds were isolated from the methanolic extract of the plant. The isolated compounds include six flavonoid compounds identified as rutin (1), quercetin-3-O-neohesperidoside (2), quercetin-3-O-β-galactoside (3), isoquercitrin (4), quercetin (5), and kaempferol 3-O-β-glucoside (6), in addition to a coumarin, scopoletin (7). The structures of the compounds were elucidated based on 1D NMR spectroscopy and high-resolution mass spectrometry (HR-MS), and by comparison with data reported in the literature. The first five compounds were selected for in vivo investigation of their anti-inflammatory and antioxidant properties in a rat model of type 2 diabetes. All tested compounds significantly reduced oxidative stress and increased erythrocyte lysate levels of antioxidant enzymes, along with the amelioration of the serum levels of inflammatory markers. Upregulation of miR-146a expression and downregulation of nuclear factor kappa B (NF-κB) expression were detected in the liver and adipose tissue of rats treated with the isolated flavonoids. Results from the biological investigation and those from the validated molecular modeling approach on two biological targets of the NF-κB pathway managed to highlight the superior anti-inflammatory activity of quercetin-3-O-galactoside (3) and quercetin (5), as compared to other bioactive metabolites.